Informed Information Design - Koessler, Frédéric; Skreta, Vasiliki (Journal of Political Economy, 2023)
We study informed persuasion, whereby a privately informed designer without ex ante commitment power chooses disclosure mechanisms to influence agents’ actions. We characterize the subset of Bayes-correlated equilibria yielding every designer type a payoff higher than what they could get from any disclosure mechanism with credible beliefs. This set of interim-optimal mechanisms is nonempty and tractable, and all its elements are perfect Bayesian equilibrium mechanisms of the informed-designer game. Interim-optimal mechanisms are characterized via belief-based approaches in pure persuasion settings. We identify single- and multiagent interactive environments in which ex ante–optimal mechanisms are interim optimal.